Acoustical maging : Volume 31 - Litniewski, Jerzy; Kujawska, Tamara; Nowicki, Andrzej (Acoustical Imaging, 2012)
The International Symposium on Acoustical Imaging is a unique forum for advanced research, covering new technologies, developments, methods and theories in all areas of acoustics. This interdisciplinary Symposium has been taking place continuously since 1968. In the course of the years the proceedings volumes in the Acoustical Imaging Series have become a reference for cutting-edge research in the field. In 2011 the 31st International Symposium on Acoustical Imaging was held in Warsaw, Poland, April 10-13. Offering both a broad perspective on the state-of-the-art as well as  in-depth research contributions by the specialists in the field, this Volume 31 in the Series contains an excellent collection of papers in six major categories: Biological and Medical Imaging Physics and Mathematics of Acoustical Imaging Acoustic Microscopy Transducers and Arrays Nondestructive Evaluation and Industrial Applications Underwater Imaging